Captioning and grammar learning in the L2 Spanish classroom. Issue 4 (8th August 2019) - Cintrón-Valentín, Myrna; García-Amaya, Lorenzo; Ellis, Nick C.
ABSTRACT: Previous research has demonstrated the effectiveness of captioning in second language (L2) comprehension and vocabulary learning. However, little attention has been paid to its potential in supporting grammar development, another challenging area in L2 acquisition. In this research, we used a randomised control design to investigate the role of salience-raising through textually enhanced captioned video on L2 vocabulary and grammar development. The experiment for this study was integrated into a one-semester university L2 Spanish grammar course. Through four data-collection sessions, we targeted: the preterite/imperfect, copula verbs, gustar -type verbs, and the subjunctive. In each session, participants saw a short grammar lesson before an animated video, which included: (i) captions with textually enhanced target vocabulary, (ii) textually enhanced target grammar, or (ii) a no captioning control. Learners were then tested on their recognition and production of the target items. Results show clear effects of captioning on vocabulary performance. For some grammar structures, there were also positive effects of captioning on production, whereas for other grammar structures no such effect was uncovered. Altogether, these findings confirm the effectiveness of captioning on vocabulary, and illustrate specific difficulties related to grammar captioning, such as the role of structure-specific saliency in the grammatical input.